Psychosocial and Behavioral Aspects of Pain and Perception of Oral Health - Zucoloto, Miriane Lucindo [UNESP]; Maroco, Joao; Duarte Bonini Campos, Juliana Alvares [UNESP] (Quintessence Publishing Co Inc, 2017)
Aims: To evaluate the contribution of the psychosocial and behavioral aspects of pain to the perception of oral health in a sample of Brazilian dental patients. Methods: This cross-sectional study involved 436 patients who sought dental care in the School of Dentistry of Sao Paulo State University and who reported some type of orofacial pain. The study group's mean age (+/- standard deviation [SD]) was 39.9 +/- 13.6 years, and the sample was 74.5% female. The Portuguese version of the Oral Health Impact Profile Short Form (OHIP-14) and the Multidimensional Pain Inventory (MPI) were used. The data were included in a structural equation model in which perception of oral health was considered the dependent variable. The evaluation of the contribution of psychosocial and behavioral aspects of pain to the perception of oral health was based on the statistical significance of causal paths (beta) evaluated by z tests (alpha = 5%). Results: The fit of the models of OHIP-14 and MPI were adequate. Interference, self-control, negative mood, and punishing responses provided significant contributions to the perception of oral health. The structural model presented adequate fit to the data (explained variance = 28.0%). Conclusion: These findings provide evidence that psychosocial and behavioral aspects of pain such as interference of pain in activities, self-control, negative mood, and punishing responses contribute to the perception of oral health.
Keywords: facial pain; oral health; pain; perception; psychosocial impact